Development of Android-Based Smart Learning Media for the Operating Systems Course Using the ADDIE Model - Kurnia Wahyu Prima; Hariyadi; Ayu Hasnining (Journal of Deep Learning, Computer Vision, and Digital Image Processing, 2026)
Purpose – The rapid advancement of digital technology has encouraged higher education institutions to integrate innovative learning media to enhance the quality of the teaching and learning process. However, learning activities in Operating Systems courses are still predominantly conducted using conventional methods, causing students to experience difficulties in understanding abstract concepts such as process management, memory management, CPU scheduling, and file systems. This study aims to develop Android-Based Smart Learning media for the Operating Systems course and to determine the feasibility level of the developed media as an interactive learning tool.Method – This study employed a Research and Development (R&D) approach using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The developed product was validated by subject-matter experts and media experts before being implemented with students of the Informatics and Computer Engineering Education Program who were enrolled in the Operating Systems course. Data were collected through validation sheets and student response questionnaires using a five-point Likert scale and were analyzed using descriptive quantitative methods.Results – The findings indicate that the Android-Based Smart Learning media was successfully developed by integrating learning materials, instructional videos, interactive quizzes, and automated feedback features into a single Android application. The material expert validation yielded a score of 89.00%, while the media expert validation achieved a score of 90.00%, both categorized as highly feasible. Furthermore, student responses obtained an average percentage of 90.27%, classified as very good. Therefore, the developed media was considered suitable for supporting the learning process in the Operating Systems course.Research Implications – This study was limited to a single study program and Android devices; therefore, the generalizability of the findings remains limited.Originality – This research integrates the concepts of mobile learning and smart learning into a single interactive learning medium specifically designed to support Operating Systems education in higher education institutions.